The impact of nonlinear pedagogy on the acquisition of power clean for athletes - Ang, Derrick Ter Quan (Nanyang Technological University, 2022)
Nonlinear Pedagogy (NLP) is a framework accounting for nonlinearity in learning and advocates infusion of variability in practice to cultivate individualised functional movement patterns. Previous research in Singapore has shown the effectiveness of NLP on open, game-like skills however, research on self-paced sports (e.g., weightlifting) is lacking. Thus, this intra-individual study investigated the impact of a four-week NLP intervention on acquisition of power clean for athletes. Six male athletes (24 ± 2.6 years) completed 11 sessions of power clean with intervention load at 70% of their One-repetition maximum (1RM). Analogy-based cues and two task constraints were included to induce perturbations and stimulate exploratory behaviour during intervention. Both performance (barbell kinematics) and movement behavioural metrics were used to quantify learning. 1RM scores were compared as the pretest, post-test, and retention assessment. Horizontal barbell displacement was calculated for barbell kinematics. Joint angle data from Perception Neuron Pro sensors were time-normalised and hierarchical clustering (Ward’s algorithm) was performed. Post-test (72.9 ± 11.3 kg) and retention (75.0 ± 13.5 kg) mean 1RM increased. A One-way ANOVA revealed mean barbell displacement did not differ significantly between sessions (F(4, 25), p = .263). Movement data from participants showed diversification of movement patterns and increased exploratory behaviour attributable to constraints manipulation. In summary, NLP proved beneficial in modifying movement behaviour and fostering exploration. Findings from this study suggest NLP can have a positive impact on self-paced skill acquisition. Practitioners can implement the approach in this study to help learners master similarly sophisticated weightlifting techniques and/or self-paced sports.